Bone marrow aplasia associated with Turner syndrome in pediatric patients - Liliana Martínez Cárdenas; Tamara Cedré Hernández; Yamel Cabrera Peña (Acta Médica del Centro, 2011)
The association of bone marrow aplasia and Turner syndrome is hardly mentioned in scientific literature. The case of a 12-year female patient that begins with fever and wet cough with yellowish expectoration and hemoptysis is reported. The patient showed a deterioration of the general condition and cutaneous-mucosal pallor. She underwent a chest radiograph that showed lesions of pneumonic aspect. Physical examination showed phenotypic abnormalities that are typical of Turner syndrome, which were confirmed by cytogenetic examination. In addition, hematological examination and bone marrow biopsy results were consistent with bone marrow aplasia. Based on the analysis of the clinical symptoms and other examinations conducted, it was concluded that the diagnosis of the patient's disease was bone marrow aplasia associated with Turner syndrome. This is the first report in Cuba of the association of these two illnesses.